BEBERAPA CATATAN TENTANG LAHIR DAN KINERJA MAHKAMAH KONSTITUSI DALAM SISTEM KEKUASAAN KEHAKIMAN INDONESIA - Aziz, HM (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Judicial review was actually initiated by Muhammad YaminBPUPKI Meeting in 1945 but was not accepted. Judicial reviewis one of the authorities of the Constitutional Court (MK), theidea can be considered as the forerunner of the Court. In 1949KRIS established a place for judicial review in the form ofconstitutional review of legislation, local levels of the stateconstitution, while the Federal law can not be contested, andcontinued in the 1950 Constitution, as a reflection of the system/ understanding of parliamentary supremacy. The idearesurfaced at the end of the Old Order government but in theform of legislative review/political review of the MPRS, but MPRSfailed to make it happen. It was not until the reform era in the2000 legislative review manifested through TAP MPR No. III/MPR/2000, then with the establishment of the ConstitutionalCourt on the 1945 changes in 2001-2002 have a concrete formand translated into Law Number 24 Year 2003 concerning theConstitutional Court. In a short time the Court as one of theprincipals of judicial power grows and develops into adistinguished institution and the state can resolve the politicalissues and constitutional law including dispute resolution interstate authority, disputes the general election (legislative andpresidential election/vice president), and testing legislationrelative decision acceptable to all parties to the dispute, becauseit is considered quite fair and balanced, and does not causesocial and political upheavals in society. Also related to therespect, protection and enforcement of human rights is a basicright for citizens, among other things during to sham deathpolitically and civil.